Designing and Measuring the Validity and Reliability of a Questionnaire on the Factors Affecting the Use of Packed Bread Compared to Non-packed Bread Using the Reasoned Action Theory - simin haghravan; mohammad alizadeh; elahe forumandi; mahsa mohajeri (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: Bread is of particular importance as a supplier of portions of calories, proteins, vitamins, and minerals needed by the body. According to the reasoned action theory, attitudes and subjective norms are factors that influence the individual's intention to do one's behavior and ultimately to do that behavior. Since consumers prefer packed bread to non-packed bread, we aimed to design a valid questionnaire on the factors affecting the use of packed bread compared to non-packed using the reasoned action theory. Methods: This was a cross-sectional, descriptive, analytical study. We designed a questionnaire according to the theory of reasoned action and based on three sessions of focused group discussion and interviews with nutrition specialists. Content and face validity of the scale was established by a panel of 11 experts. To confirm the reliability of the scale, Cronbach's alpha coefficient was applied. Results: The first draft of the questionnaire contained 51 items. After determining the validity and reliability of the items, 44 items remained, 17 of which were on attitude, 10 on subjective norms, 9 on behavioral intention, and 8 on nutritional behavior. For the final  questionnaire, the average content validity index was calculated to be 0.90 and Cronbach's Alpha coefficient was 0.83. Conclusion: The results suggested that the developed questionnaire is a valid and reliable tool, and it can be used to identify the factors affecting consumers' preferences regarding the use of packed bread compared to non-packed bread using the reasoned action theory.